Asymmetric synthesis and structure-activity studies of the fungal metabolites colletorin A, colletochlorin A and their halogenates analogues. Issue 28 (12th July 2018) - Marsico, Giulia; Pignataro, Barbara A.; Masi, Marco; Evidente, Antonio; Casella, Francesca; Zonno, Maria Chiara; Tak, Jun-Hyung; Bloomquist, Jeffrey R.; Superchi, Stefano; Scafato, Patrizia
Abstract: The first asymmetric total synthesis of both enantiomers of the natural products colletorin A and colletochlorin A is presented. The proposed methodology is based on the coupling reaction between highly substituted aromatic Gilman cuprates and optically active allyl bromides, in turn obtained by Sharpless asymmetric dihydroxylation. The latter ensured a high degree of regio- and stereocontrol in the enantioselective step of the synthesis. The same synthetic strategy has been also applied for the preparation of differently halogenated synthetic analogues of colletochlorin A in high enantiomeric purity. The enantioselective synthesis of colletorin A and colletochlorin A allows to reliably assign their absolute configuration. Preliminary assessment of their herbicidal and insecticidal properties evidence the possibility to modulate the bioactivity of these compounds, highlighting its dependence on both the absolute stereochemistry and the halogen nature. Graphical abstract: Image 1